Proposal of a minimally invasive approach diagnosing desquamative gingivitis-associated diseases - Marco Túllio Brazão-Silva; Lioney Nobre Cabral; Tiago Novaes Pinheiro (Wolters Kluwer Medknow Publications, 2021)
Background: We aimed to present a minimally invasive clinical approach to collect a suitable sample for the laboratory diagnosis of desquamative gingivitis. Materials and Methods: The proposed technique involves Nikolsky's test for the collection of tissue samples. It consists of the histopathological analysis of the bullous membrane formed in cases with positive Nikolsky's sign (NS). Three patients without a previous diagnosis of the disease agreed to undergo this protocol before a biopsy. Results: The diagnoses of the three cases reported here were mucous pemphigoid (MP), pemphigus vulgaris (PV), and lichen planus (LP). The tissue samples collected using this technique were sufficient to microscopically observe partial-thickness epithelium (diagnosing PV) or full-thickness epithelium (diagnosing MP). The diagnosis of LP was only possible by conventional biopsy. Conclusion: We observed, for different cases, some advantages of the proposed technique: minimally invasive, potentially superior to exfoliative cytology, easily performed, and with low costs.